1982
DOI: 10.1093/nar/10.19.5809
|View full text |Cite
|
Sign up to set email alerts
|

The molecular cloning and characterisation of cDNA coding for the α subunit of the acetyl-choline receptor

Abstract: A rare cDNA coding for most of the alpha subunit of the Torpedo nicotinic acetylcholine receptor has been cloned into bacteria. The use of a mismatched oligonucleotide primer of reverse transcriptase facilitated the design of an efficient, specific probe for recombinant bacteria. DNA sequence analysis has enabled the elucidation of a large part of the polypeptide primary sequence which is discussed in relation to its acetylcholine binding activity and the location of receptor within the plasma membrane. When u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(58 citation statements)
references
References 26 publications
2
55
0
1
Order By: Relevance
“…The teams of Shosaku Numa (38 -40), Stephen Heinemann (41,42), and Eric Barnard (43), as well as Anne Devillers-Thiéry, and Jérôme Giraudat (44,45) in my laboratory, struggled to clone the complementary DNAs of the different subunits from electric organ and muscle and to establish their complete sequence. Experiments by Eric Barnard and Ricardo Miledi had demonstrated that messenger RNA extracted from the electric organ of Torpedo injected into Xenopus oocytes led to the synthesis and incorporation of functional AChRs into the membrane of the oocyte (46).…”
Section: The Pentameric Organization Of the Nicotinic Receptor And Thmentioning
confidence: 99%
“…The teams of Shosaku Numa (38 -40), Stephen Heinemann (41,42), and Eric Barnard (43), as well as Anne Devillers-Thiéry, and Jérôme Giraudat (44,45) in my laboratory, struggled to clone the complementary DNAs of the different subunits from electric organ and muscle and to establish their complete sequence. Experiments by Eric Barnard and Ricardo Miledi had demonstrated that messenger RNA extracted from the electric organ of Torpedo injected into Xenopus oocytes led to the synthesis and incorporation of functional AChRs into the membrane of the oocyte (46).…”
Section: The Pentameric Organization Of the Nicotinic Receptor And Thmentioning
confidence: 99%
“…Several laboratories recently succeeded in cloning and sequencing some (6)(7)(8)(9) or all (10)(11)(12) of the cDNAs encoding the four subunits of Torpedo AcChoR. It was found that there is significantly more homology between the deduced protein sequences of the a-,8 and y-8 pairs than between any other combinations of subunits, suggesting that an initial duplication of the ancestral gene had given rise to two protogenes, one of which later yielded the y and 8 genes while the other gave rise to the a and p genes (12).…”
mentioning
confidence: 99%
“…Our recent studies have elucidated the primary structures of all four subunits of the Torpedo calijornica acetylcholine receptor by cloning and sequencing cDNAs encoding the respective subunit precursors [4 -61; cDNA sequences for the y subunit precursor of the T.caliJornica receptor [7] and the M subunit precursor of the Torpedo murmorata receptor [8,91 have also been reported by other groups. Conspicuous amino acid sequence homology is found among the four subunits of the T. caliJornica acetylcholine receptor, suggesting that the genes encoding them have been generated from a single common ancestor by gene duplications.…”
mentioning
confidence: 99%